Aprendizagem da língua inglesa como terceira língua (L3) por aprendizes surdos brasileiros: investigando a transferência léxico-semântica entre línguas de modalidades diferentes - Silva, Maria Clara Corsini (2013)
Research in the area of third language (L3) acquisition is still preliminary if compared to the studies on bilingual acquisition. If studies about multilingual acquisition carried out with hearing participants users of oral languages are incipient, they are even rarer with deaf learners of oral third languages because very little has been investigated so far. The present study aims at analyzing how deaf Brazilian learners of the English Language (EL) as a L3 learn English. By doing so, we try to investigate the role played by lexical and semantic transfer of the two languages previously learned Brazilian Sign Language (LIBRAS) and the Portuguese Language (PL) on the lexicon of the EL. For that purpose, this study will analyze the data collected among 9 deaf young and adult students of elementary school, students of the public system, users of LIBRAS as a mother tongue (L1) in an intermediate level, learners of PL as a second language (L2) in a basic level and beginners of EL as a L3. Having in mind the main objective of this study, we try to investigate the following: if a process of lexical transfer also occurs in languages of different modalities (sign and oral languages); if there is evidence of lexical transfer of the languages previously learned (LIBRAS and PL) on the EL and if there is a relationship between the proficiency level acquired in the previous languages (LIBRAS and PL) on the lexical and semantic acquisition of the EL. This study also searches to examine the kinds of mistakes most commonly made by deaf learners of EL (L3) whose L1 is LIBRAS and also the mistakes most frequently made by these students who are also learners of the PL as L2. The data concerning the five objectives were obtained by means of four different lexical tasks involving the participants three languages. In order to collect data, the software E-Prime was used in the first three tasks, the last one was a word production task in EL. Information of the first and second objectives of this study showed that there is a partial transfer of lexical items from a sign (LIBRAS) to an oral language (EL). Data related to the third objective demonstrated that LIBRAS (L1), more stable language, plays a more influential role than PL (L2) in transferring its linguistic elements to EL (L3). The fourth objective suggested that deaf learners of the EL as a L3, native users of LIBRAS tend to make phonological mistakes or mistakes due to the relation between fingerspelling and the first letter of the written word, but this kind of transfer does not always occur. The fifth objective indicated that deaf learners of the EL (L3) are likely to transfer linguistic items from the LP (L2) to the EL (L3), at least partially. In sum, the results of the present study are similar to researches conducted with oral languages and hearing participants according to which all languages are active in a bilingual/multilingual s mind.